Lifor Solution: An Alternative Preservation Solution in Small Bowel Transplantation - Mingxiao Guo; Chunlei Lu; Ying Gao; Haifeng Zhang; Dongfeng Chen; Yousheng Li (Gastroenterology Research and Practice)
Background and Objectives. The intestinal mucosa is extremely sensitive to ischemia. Better intestinal preservation is the first step to improve the results of intestinal transplantation. The aim of the study is to investigate the effect of cold Lifor solution on preservation of swine small bowel. Methods. Swine ileum segments (200 cm) were allotransplanted heterotopically after 9-hour cold storage with UW solution (group 1, n=6), with Lifor solution (group 2, n=6), or without storage (group 3, n=6), respectively. After cold storage, mucosal adenosine triphosphate (ATP) concentrations and histopathologic analysis after preservation were performed. At day 7 after the transplantation, intestinal absorptive function was also observed. Results. After 9 h cold preservation, pathological changes, the content of ATP in the intestinal mucosa, and the intestinal absorptive function after transplantation in group 2 were similar to those of group 1. Conclusion. The effect of cold storage of swine small bowel with Lifor solution is similar to that of UW solution. It may provide additional rationale for further exploration of Lifor as an alternative preservation solution in small bowel transplantation.